Optimizing statistics education: Analyzing students' perceptions of SPSS usage - Cipta, Eliva Sukma; Suryadi, Didi; Herman, Tatang; Al Jupri; Maulana, Dick Dick (Universitas Papua, 2025)
The integration of statistical software such as SPSS in higher education represents a pivotal advancement, yet limited research has systematically examined how students perceive its pedagogical usefulness and accessibility. Prior studies seldom differentiate between the cognitive and affective dimensions influencing the efficacy of SPSS-assisted learning, leaving a gap in understanding its broader impact on student engagement and competence. Addressing this gap, the present research investigates the novelty of SPSS implementation within statistics coursework, focusing specifically on student perceptions regarding its usefulness and ease of use. Employing a descriptive mixed-methods approach, quantitative data were collected from 85 respondents through a validated and reliable questionnaire comprising 13 items, complemented by qualitative insights from in-depth interviews using open-ended prompts. The findings indicate that student perceptions are predominantly favorable for both usefulness (79.21%) and ease of use (75.18%). Qualitative analysis substantiates these results, highlighting accelerated data analysis, simplified processing, and enhanced visualization as key strengths, while noting initial challenges faced by some participants. The study underscores that optimizing the educational value of SPSS necessitates comprehensive instructional support, thereby informing future curricular improvements designed to foster numeracy and analytical proficiency in statistical learning.